ln(6-2x)=ln(3x-1)+ln(x+4)

Simple and best practice solution for ln(6-2x)=ln(3x-1)+ln(x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(6-2x)=ln(3x-1)+ln(x+4) equation:


Simplifying
ln(6 + -2x) = ln(3x + -1) + ln(x + 4)
(6 * ln + -2x * ln) = ln(3x + -1) + ln(x + 4)
(6ln + -2lnx) = ln(3x + -1) + ln(x + 4)

Reorder the terms:
6ln + -2lnx = ln(-1 + 3x) + ln(x + 4)
6ln + -2lnx = (-1 * ln + 3x * ln) + ln(x + 4)
6ln + -2lnx = (-1ln + 3lnx) + ln(x + 4)

Reorder the terms:
6ln + -2lnx = -1ln + 3lnx + ln(4 + x)
6ln + -2lnx = -1ln + 3lnx + (4 * ln + x * ln)
6ln + -2lnx = -1ln + 3lnx + (4ln + lnx)

Reorder the terms:
6ln + -2lnx = -1ln + 4ln + 3lnx + lnx

Combine like terms: -1ln + 4ln = 3ln
6ln + -2lnx = 3ln + 3lnx + lnx

Combine like terms: 3lnx + lnx = 4lnx
6ln + -2lnx = 3ln + 4lnx

Solving
6ln + -2lnx = 3ln + 4lnx

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '-3ln' to each side of the equation.
6ln + -3ln + -2lnx = 3ln + -3ln + 4lnx

Combine like terms: 6ln + -3ln = 3ln
3ln + -2lnx = 3ln + -3ln + 4lnx

Combine like terms: 3ln + -3ln = 0
3ln + -2lnx = 0 + 4lnx
3ln + -2lnx = 4lnx

Add '-4lnx' to each side of the equation.
3ln + -2lnx + -4lnx = 4lnx + -4lnx

Combine like terms: -2lnx + -4lnx = -6lnx
3ln + -6lnx = 4lnx + -4lnx

Combine like terms: 4lnx + -4lnx = 0
3ln + -6lnx = 0

Factor out the Greatest Common Factor (GCF), '3ln'.
3ln(1 + -2x) = 0

Ignore the factor 3.

Subproblem 1

Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(1 + -2x)' equal to zero and attempt to solve: Simplifying 1 + -2x = 0 Solving 1 + -2x = 0 Move all terms containing l to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2x = 0 + -1 -2x = 0 + -1 Combine like terms: 0 + -1 = -1 -2x = -1 Add '2x' to each side of the equation. -2x + 2x = -1 + 2x Combine like terms: -2x + 2x = 0 0 = -1 + 2x Simplifying 0 = -1 + 2x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| I=(118*2000)-235670 | | 8+2x*4=x*5+11 | | 0.12(18)+0.03x=0.06(18+x) | | n=0.04*2002-78.64 | | 2[5(11-2)]-16= | | i=103*2000-205604 | | 3(2-5)=n+3 | | 7x=1/49 | | i=112*2004-223617 | | i=112x-223617 | | -4(5n+3)=4 | | 16x^2-8x-49=0 | | 2x^2-2x+5.5=8 | | 2x^2-2x+5.5=6 | | 2x^2-2x+5.5=2 | | 2x^2-2x+5.5=4 | | 2x^2-2+5.5=4 | | 2x^2+x=7 | | 65-6x=3x+19 | | 2x^2-2+5.5=2 | | 4x^2-20x+19=0 | | y=2x^2+8+6 | | 4+2x+2=2x | | y-1+2y-5=3y-9 | | 0.20(6)+0.05x=0.10(24+x) | | 3x(x-2)(2x+1)=0 | | -99-8=7x+21 | | 7-10x=131-38x | | 103-3x=15x+23 | | .44y^2+1=0 | | 3(y+2)-2=2(4-y) | | 3(y+2)-2=2(41y) |

Equations solver categories